Damage of brown planthopper (BPH) Nilaparvata lugens and rice leaf folder (LF) Cnaphalocrocis medinalis in parent plants lead to distinct resistance in ratoon rice. (31st December 2022) - Deng, Qian-Qian; Ye, Mao; Wu, Xiao-Bao; Song, Jia; Wang, Jun; Chen, Li-Na; Zhu, Zhong-Yan; Xie, Jing
ABSTRACT: Herbivore-induced defense responses are often specific, whereas plants could induce distinct defense responses corresponding to infestation by different herbivorous insects. Brown plant hopper (BPH) Nilaparvata lugens, a phloem-feeding insect, and rice leaf folder (LF) Cnaphalocrocis medinalis, a chewing insect, are both specialist herbivores on rice. To characterize the distinct resistance primed by prior damage to these two specialist herbivores, we challenged rice plants with two herbivores during vegetative growth of parent plants and assessed plant resistance in subsequent ratoons. Here, we show that LF and BPH induce different suites of defense responses in parent rice plants, LF induced higher level of JA accumulation and OsAOS, OsCOI1 transcripts, while BPH induced higher accumulation of SA and OsPAL1 transcripts. Moreover, an apparent loss of LF resistance was observed in OsAOS, OsCOI1 RNAi lines. Ratoon plants generated from parents receiving prior LF infestation exhibited higher jasmonic acid (JA) levels and elevated levels of transcripts of defense-related genes associated with JA signaling, while ratoon generated from parents receiving prior BPH infestation exhibited higher salicylic acid (SA) levels and elevated levels of transcripts of defense-related genes associated with SA signaling. Moreover, previous LF infestation obviously elevated ratoons resistance to LF, while previous infestation by BPH led to enhanced resistance in ratoons to BPH. Pre-priming of ratoons defense to LF was significantly reduced in OsAOS and OsCOI1 RNAi plant, but silencing OsAOS and OsCOI1 did not attenuate ratoons resistance to BPH. These results suggest that infestation of two specialist herbivores with different feeding styles in parent crop led to distinct defense responses in subsequent rations, and the acquired resistance to LF in ratoons is associated with priming of jasmonic acid-dependent defense responses.